ANALYSIS OF PROVIDING INCENTIVES IN INCREASING EMPLOYEE LOYALTY AT PT. SUNAN RUBBER - Dita Novitasari; Dian Utari; Debi Carolina; Muhammad Furqon (Jurnal Manajemen, 2024)
Abstract: Employees of PT Sunan Rubber receive monthly and yearly rewards based on their performance and working hours. If the production department meets its goals, it will receive additional rewards. On the other hand, personnel who are on probation, perform poorly, visit infrequently, or are taken over by management are not given any incentives. The purpose of this study is to ascertain how offering incentives can boost worker loyalty. The investigation was carried out at PT Sunan Rubber, with the aim of examining the workers in the production division of the company. In this study, primary and secondary data sources were used. Literature reviews, surveys, and interviews are the methods utilized to collect data. Purposive sampling, which looks at the criteria for respondents based on gender, age, most recent education, and duration of service, is the sample technique employed in this study. There were 54 responders in the sample that this study utilized. This study employs a qualitative approach along with descriptive analysis. Given that both variables scored in the "very good" range, it is anticipated that offering incentives will stimulate staff members and foster a greater sense of commitment to the organization. This is evident from the 82.4% incentive provision rate and the 85.6% employee loyalty percentage of the outcomes.